Bullying en escolares de la Unidad Educativa Marietade Veintimilla de la ciudad de Loja. - Paccha León, Segundo Manuel (2018)
The present dissertation work was done in order to know the measure of Bullying, school bullying or violence between equals. Bullying is a phenomenon that is present in schoolchildren, and currently represents a risk for the integral development of children, leading them to future problems related to their psychological development. This research results from a quantitative study with a descriptive and transversal approach, in which information has been collected from 392 schoolchildren from the third year to the seventh year of basic general education who study in the Educational Unit Marieta de Veintimilla of Loja city. The results obtained after analyzing the surveys indicate that the phenomenon of Bullying exists in the school children of the educational unit, which in turn reflects the presence of violence among them, this being a risk factor for their normal psychosocial development. In addition, making a comparison with the studies conducted in other countries such as Colombia and Brazil, it was observed that children were victims of harassment by their peers, at least once throughout the course of their studies within their school or high school. Keywords: Bullying, schoolchildren, violence, violence among peers.